Time Coding-Based Single-Photon-Counting Lidar for Obtaining Spatial Location - Hanfu Zhang; Jie Liu; Qichang An; Jianli Wang (Photonics, 2023)
This paper proposes a single-photon-counting lidar based on time coding that can obtain the target’s spatial location and measure the distance and azimuth angle in real time without needing a scanning device. Multiple optical fibers were used to introduce laser echo photons into a single-pixel single-photon detector. According to the deviation in the detection time of the echo photons passing through different optical fibers, multiple distances can be obtained simultaneously. Combining the measured distances with the fiber spacing allows the calculation of the distance, azimuth angle, and spatial coordinates of the target. This lidar has the advantages of high photon detection efficiency, short signal acquisition time, and low cost compared to array detectors.